PENGARUH SENAM KAKI TERHADAP PERUBAHAN GLUKOSA PADA PASIEN DIABETES MELITUS TIPE 2 DI LINGKUNGAN STIKES SANTA ELISABETH MEDAN TAHUN 2017 - Mestiana Br. Karo; Lilis Novitarum; Maria Uli Marselina Saragih (Elisabeth Health Jurnal, 2018)
Gymnastics is a series of movements that require strength, regular speed, which is done independently or in groups with the aim of improving health in the body, and self-confidence. The type of exercise that can be recommended for someone who has a history of type 2 diabetes mellitus is foot gymnastics. Gymnastics is an activity or physical exercise to prevent injuries and help smooth blood circulation of legs and easy to do by many people, this leg aerobic aims to improve blood circulation, strengthen the small muscles in the legs, prevent foot and foot deformities can lower glucose.Goals : The purposed of this study to determine the effect of foot gymnastics on changes in glucose.Methods : The design of this research is pre experiment with one group pre post test designapproach. Sampling technique purposive sampling, with the number of samples of 10 respondents. Measuring tool used is observation sheet and SOP. Data analysis was performed by using Wilcoxon Sign Rank Test with p = 0,008 (<0,05).Result : This shows that there is influence of foot gym on glucose change in patients with type 2 diabetes mellitus in STIKes Santa Elisabeth Medan Environment.Conclution : It is hoped that diabetes mellitus type 2 can perform foot exercises anywhere and anytime as an effort to help improve blood circulation, keeping blood sugar always in a normal state.